Penyuluhan Kenakalan Remaja dan HIV/AIDS dalam Meningkatkan Pengetahuan dan Peran Remaja di SMA Muhammadiyah 1 Kabupaten Malang - Endah Sri Wulandari; Dini Ria Oktavia (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2024)
Community service in this activity has the aim of increasing the knowledge and role of adolescents about the dangers of juvenile delinquency which has a high risk of causing HIV / AIDS and has an impact on the future of adolescents. Adolescence is an age that is experiencing increased vulnerability to various health risks, especially those related to juvenile delinquency and reproduction, including the increased threat of HIV/AIDS. Human Immunodeficiency Virus (HIV) is a group of retroviruses that can duplicate, print, and insert genetic material to cause Acquired Immunodeficiency Syndrome (AIDS). This disease can weaken a person's immune system and cause opportunistic infections. The method used in this activity is in the form of lectures by providing counseling on the dangers of HIV/AIDS and juvenile delinquency. Students were given counseling using PowerPoint media and videos. Then participants were allowed to ask questions and formed 3 discussion groups to discuss issues related to juvenile delinquency. Participants were students of SMA Muhammadiyah 1 Kepanjen.